Effectiveness of Zero Based Waste Management Policy in Realizing a Clean Gresik Regency - Hertati, Diana; Nurhadi; Tukiman (Universitas Muhammadiyah Sidoarjo, 2023)
The development of the population in an area and the existence of socio-economic activities will have an impact on increasing the type and amount of waste that will threaten the regional ecosystem. The empirical facts still reflect that waste management is not optimal with the high amount of waste entering the Ngimpik TPST, so that effective waste management is needed in realizing Gresik Regency as a clean city. This study aims to describe the Effectiveness of Waste Management based on